Optimizing the Use of Digital Branding to Increase Exports of Green Plants in International Markets - Sary, Munanda Tania; Purnomo, Hery (Proceeding Kilisuci International Conference on Economic & Business, 2025)
Research aim : identify the digital branding elements that are most influential in increasing product competitiveness in international markets. As well as providing practical recommendations for other MSMEs to optimize digital branding in the context of green plant exports. Design/Methode/Approach : This study employs a qualitative method with a case study approach, using CV Kokonat Indonesia as the main subject. Data were obtained through in-depth interviews with the business owner to explore information related to digital branding strategies, challenges, and their impact on exports, as well as through documentation that analyzed the company’s vision, mission, digital marketing strategies, and customer reviews. The research subject was selected using purposive sampling due to their direct experience in implementing digital branding for the export of tropical ornamental plants, while the research object is the digital branding strategy itself. Data were analyzed using triangulation and thematic analysis by identifying patterns based on key terms such as digital branding, customer trust, and exports, and the results are presented in narrative and table formats to clarify the relationship between the data and the main findings. Research Finding : This study found that the implementation of digital branding at CV Kokonat Indonesia plays a crucial role in increasing the export of tropical ornamental plants. The use of digital platforms such as Instagram, the official website, and international marketplaces (such as Etsy) has enhanced brand visibility and built customer trust through transparency in cultivation, packaging, and shipping processes. This strategy has helped the company boost export demand to more than 10 countries, despite facing challenges related to cultural differences and logistical constraints. Additionally, innovations such as the planned use of AR technology on the website have been identified as potential steps to strengthen customer interaction and create differentiation in the global market. Theoretical contribution/Originality : contributes to a deeper understanding of digital branding in the context of green plant exports. Practitionel/Policy implication : providing information for business actors in designing digital branding that can increase international or export competitiveness. Research limitation : the focus in only on one MSMEs, so the results cannot be fully generalized to MSMEs in other sectors.